Auditor Reputation Moderates the Impact of Tax Avoidance and Tax Compliance on Firm Value - Suwaldiman, Suwaldiman; Rheina, Adella (Penerbit Goodwood, 2023)
Purpose: This study tests and analyses the impact of tax avoidance and tax compliance on the value of firms with an auditor's reputation as a moderator in manufacturing firms listed on the Indonesia Stock Exchange in 2015-2019. Methodology/approach: The sampling technique uses purposive sampling and produces a total sample of 106 companies, resulting in 530 observation samples. The data used is Secondary data were obtained from the Indonesian Stock Exchange website and Yahoo Finance. Multiple linear regression analysis was used in this study. Results/findings: The study revealed that tax avoidance has a positive impact on firm value; tax compliance has a positive impact on firm value; the auditor's reputation does not strengthen the impact of tax avoidance on the value of the firm; and the auditor's reputation does not strengthen the impact of tax compliance on the value of the firm. Limitations: This study is limited to manufacturing firms listed on the IDX for 2015-2019. Contribution: This study contributes to investors’ investment decisions based on companies’ tax avoidance and compliance. The intensity of tax avoidance and tax compliance has been proven to affect firm value; therefore, these two variables can be used to predict firm value.